Technical and tactical aspects of blocked forehand return in the singles men - Teusdea, C. (Science, Movement & Health, 2017)
Problem statement. In the past, the return of service was considered "shot that sent the ball into the ground. Return importance has increased considerably in recent years simultaneously with the service due to rapid appearance playing surfaces, increasing execution speed of service. In actual tennis by using return can earn points in the game if executed efficiently in technically and tactically. Aim. Knowing the technical and tactical aspects of return are important in this process of learning and development especially in the children. Initiation into tennis can begin return service learning. The return service is a blow base and play an essential role in learning the game of tennis. Conclusions. Tennis game that takes place between 2-4 players or players who send the ball over the net with rockets. The return blocked right - kick return the ball served by the opponent with one hand, with a short swing motion rocket body toward the ball comes. Technical return three times blocked include training, impact and end the coup carried out uniformly. The return part of the start of the game. Tactically processes of return depending on the quality of service and subsequent actions of the server. Men's singles takes place after a certain structure of the game and the simple field with specific dimensions.